Risk Analysis of Health Workers in Slaughterhouses Due to Ammonia Gas Exposure - Umi Salamah; Retno Andriyani (JURNAL KESEHATAN LINGKUNGAN, 2018)
Slaughterhouses was one part of the livestock industry. The livestock industry was a producer of ammonia emissions in the atmosphere. Ammonia has a negative impact on public health and the environment. This study aims to analyze the health risks to workers in slaughterhouses caused by ammonia gas exposure. The research design in this research was an observational research with cross-sectional design that used environmental health risk assessment (EHRA). The population of this research was workers in slaughterhouse, technique, sanitation and IPAL that consisting of 35 peoples. The measurement of ammonia gas was calculated used Spectrophotometer-Nessler method with wavelength 440 nm. The Air samples was taken at four points in the slaughterhouses Pegirian area. The result of the research indicated that the concentration of ammonia highest in slaughterhouses Pegirian of 0.025972 ppm (0.01806 mg/m3) and concentration ammonia lowest of 0.004364 ppm (0.00303 mg/m3). Based on the analysis of environmental health risks in mind that the value of RQ by 0.002781. The conclusion of this research is the exposure to ammonia gas at-risk population with 55 Kg weight at slaughtering houses Pegirian still within safe limits for the frequency of 250 days / year to 30 years. Advice that can be given is the need to improve the management company waste management as a source of ammonia emissions in slaughterhouses.